Automation of a tree radar platform - Goh, Benjamin Wei Wen (Nanyang Technological University, 2024)
This Final Year Project (FYP) aims to design, develop, and demonstrate an automated testbed solution to accurately position and move a tree radar around trees so that the radar may scan and determine if a cavity is present within the tree trunk that may pose a risk to pedestrians. In this project, a flexible trajectory sliding platform was successfully developed with the ability to perform automated positioning and scanning along a straight and circular trajectory around a tree trunk. Additional automated test equipment to obtain sample scan data and the ground truth of tree trunk samples were also successfully developed in the form of an automated static rotator used in conjunction with an automated straight trajectory sliding platform, to obtain ideal laboratory condition B scan data for comparison with practical field measurements.